ANALISIS MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Syamsul Ma'arif Al fatah; Jupriyanto Jupriyanto; Andarini Permata Cahyaningtyas (Universitas Syiah Kuala, 2019)
This research is focused on the analysis media of interactive multimedia learning which is used in the learning process in elementary schools towards the learning motivation of students. Education becomes an important thing in everyday life. In education a lot of potential exists in a person to be developed optimally. In the education process, not only prioritizing the improvement of academic abilities, because education also requires cultural transformation, education can also be made as a long-term investment. Furthermore, at this time, it is still minimum, the reading interest index in Indonesia, based on the study of